Geomorphology and the carbon cycle - Evans, Martin 1970- (RGS-IBG book series, 2022)
"As global atmospheric carbon concentrations continue to rise, there has been an increasing focus in the 21st century on understanding terrestrial components of the carbon cycle. This has been a major interdisciplinary research agenda and advances in remote sensing and modelling of vegetation systems have developed increasingly detailed understanding of above ground carbon cycling (Fatichi et al. 2019; Lees et al. 2018). Similarly, the storage of carbon in soils below ground has been the focus of extensive and detailed research (Wiesmeier et al. 2019). However, arguably understanding of soil carbon processes lags behind analysis of above ground systems. For example, it is notable that, in the paper cited at the top of this chapter (Bloom et al. 2016), the terrestrial carbon model that the paper applies includes significant detail around the cycling of carbon through biomass, modelling carbon in leaves, roots and wood separately, whilst soil carbon represents a single store. Where more detailed models of soil carbon cycling are applied that consider multiple solid carbon pools (e.g. Abramoff et al., 2018), a notable absence is consideration of lateral transfers of organic carbon in the soil and sediment system. Over the last ten years however, there has been an increasing recognition of the importance of lateral carbon fluxes within the landscape as a key part of understanding carbon dynamics at the large scale (e.g. Battin et al. 2008). Figure 1.1 is the 5th Intergovernmental Panel on Climate Change (IPCC) representation of the terrestrial carbon cycle (IPCC 2013). Flux from the land to the oceans is represented by the fluvial carbon flux. Whilst the IPCC estimates distinguish pre-industrial and post-industrial fluxes for many of the key elements of the cycle, human impacts are not quantified for the fluvial system. Clearly, a more detailed picture of the fluvial system is required. The fluvial carbon flux is relatively small compared to the magnitude of terrestrial carbon storage, but is simply the residual of carbon transformation which occurs as organic matter is transported from headwaters to the oceanic sink. Much of the uncertainty about the relative importance of lateral carbon fluxes in the terrestrial carbon budget stems from a lack of knowledge about how large this residual is as a proportion of the total amount of organic carbon which is transported and delivered from hillslopes"--Provided by publisher.